Slovak Dairy Sheep – new composite sheep breed raised in Slovakia - Margetín, Milan; Janíček, Martin; Vavrišinová, Klára; Pavlík, Ivan; Huba, Ján; Oravcová, Marta; Hozáková, Katarína (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2020)
In the beginning of 1990–ies, the programme of formation of synthetic population of Slovak Dairy sheep (SD) was launched. The establishment of breed was divided into two periods: first, crosses of local breeds (Improved Valachian - IV, Tsigai - Ts and Merino) with improving breeds (Lacaune - LC, East Friesian - EF) of various proportions were formed; second, a close (inter se) breeding scheme within the crossbred population was applied. At present, five thousands SD ewes are included in performance testing. Milk and reproduction traits were analyzed using mixed model methodology during the period between 1995 and 2015. The standardized milk yield (SMY) and average daily milk yield (ADMY) increased more than twice: 79.8±5.36 l (1995) vs. 164.0±2.04 l (2015) and 495.1±33.5 ml (1995) vs. 1035.3±12.8 ml (2015), respectively. In ten percent of most productive ewes, SMY was equal to 257.6 l, ADMY was equal to 1604 ml and dry matter was equal to 26.6 kg. Ewes of SD have good udder traits. Litter size in top 50 % flocks is above 150 %. The population of SD was recognized as a new dairy breed in 2017. In 2017-2019 the best flocks achieved milk production higher than 220 liters. Based on a comprehensive analysis of the genetic structure of SD we found that the overall genetic proportion of improving breeds is in new breed 60%. The remaining 40% are domestic breeds, of which IV and Ts genes are represented in the SD breed at approximately the same level (18%).